Tra1 has specific regulatory roles, rather than global functions, within the SAGA co-activator complex - Helmlinger, Dominique (European Molecular Biology Organization, 2011)
The SAGA complex is a conserved, multifunctional co-activator that has broad roles in eukaryotic transcription. Previous studies suggested that Tra1, the largest SAGA component, is required either for SAGA assembly or for SAGA recruitment by DNA-bound transcriptional activators. In contrast to Saccharomyces cerevisiae and mouse, a tra1Δ mutant is viable in Schizosaccharomyces pombe, allowing us to test these issues in vivo. We find that, in a tra1Δ mutant, SAGA assembles and is recruited to some, but not all, promoters. Consistent with these findings, Tra1 regulates the expression of only a subset of SAGA-dependent genes. We previously reported that the SAGA subunits Gcn5 and Spt8 have opposing regulatory roles during S. pombe sexual differentiation. We show here that, like Gcn5, Tra1 represses this pathway, although by a distinct mechanism. Thus, our study reveals that Tra1 has specific regulatory roles, rather than global functions, within SAGA.